A nonlinear approach to the wind strength of Gothic Cathedrals: The case of Notre Dame of Paris. (15th March 2019) - Vannucci, P.; Masi, F.; Stefanou, I.
Highlights: A nonlinear incremental approach to the wind strength of a Gothic Cathedral. The diagram wind-pressure-displacement of the building. The failure mechanism automatically determined by the propagation of the damage. Abstract: The problem of assessing the strength to wind actions of Gothic Cathedrals is addressed in this paper. A nonlinear approach, based upon a large-strain, large displacements formulation and using a nonlinear constitutive law modeling the no-tension behavior of the material as a damage law is proposed. The method is applied to the study of the Cathedral Notre Dame of Paris.